Feasibility Of Complementary Metal Oxide Semiconductor (Cmos)-Based Time-Of-Flight (Tof) Image Sensors In Conjunction With Kilovoltage (Kv) Cone Beam Computed Tomography (Cbct) For Real-Time Tumour Tracking In Radiotherapy - Lim, Siew Yong @ Siew Eng (2022)
Respiratory induced tumour movement is one of the main causes of error in thoracic radiotherapy. The tumour movement may results in sub-optimal delivery of radiation to the target during treatment. The objective of this research is to investigate the feasibility of two Complementary Metal Oxide Semiconductor (CMOS)-based Time-of-Flight (ToF) image sensors in conjunction with kilovoltage (kV) cone-beam computed tomography (CBCT) imaging system for real-time tumour tracking in radiotherapy. A dynamic phantom was designed to simulate the periodic breathing motion of patient. Two ToF image sensors (Argos3D P320 & P330, BECOM Electronics, Austria) of different pixel array size and type of illumination system were employed.